2019
DOI: 10.1016/j.soildyn.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Seismic risk at urban scale: the role of site response analysis

Abstract: A refined seismic risk assessment at urban level is fundamental to identify the most correct risk mitigation policies, both in short and long terms. To date, seismic risk assessment frameworks at regional level consider the site response by means of simplified geotechnical analyses. This study investigates how different procedures of site response analysis influence the risk quantification at urban scale. Simplified and refined analyses are computed and compared for the urban area of Benvento, Italy. For the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…The results show well agreements between the calculated and theoretical values with the maximum error less than 1 Hz, which means the adjustment to fit SA rock and has limited disturbance on . The distribution of PGA amplification factors [15] as a function of with different shaking intensities and site conditions are plotted in Figure 12A. Regardless of the PGA rock level and site condition, similar second-order polynomial relationships between the mean PGA surf and mean can be fitted (Figure 12A).…”
Section: Frequency Contentsmentioning
confidence: 83%
See 1 more Smart Citation
“…The results show well agreements between the calculated and theoretical values with the maximum error less than 1 Hz, which means the adjustment to fit SA rock and has limited disturbance on . The distribution of PGA amplification factors [15] as a function of with different shaking intensities and site conditions are plotted in Figure 12A. Regardless of the PGA rock level and site condition, similar second-order polynomial relationships between the mean PGA surf and mean can be fitted (Figure 12A).…”
Section: Frequency Contentsmentioning
confidence: 83%
“…This can be achieved by directly simulating ground motions using hazard spectrum with adjusted amplitude. However, De Risi et al [15] showed that a simplified method for site effects could be unreliable. Besides, for some region like China, the local ground-motion prediction equation (GMPE) only provide ground-motion intensities on bedrock [16].…”
Section: Introductionmentioning
confidence: 99%
“…Then, an equivalent linear analysis was performed using the code DEEPSOIL 82 to deconvolve the selected records through the soil to establish the 'bedrock motion' 78 . This was done considering an initial damping ratio of 2% in softer layers and 0.5% in harder layers 83 and using the Seed and Idriss 1991 shear modulus reduction and material damping curves for sand as per DEEPSOIL option 84 . Figure 6A depicts the acceleration response spectra of the deconvolved input motions used in the experimental tests, in the unscaled (solid lines) and scaled (dashed line) case, respectively.…”
Section: Physical Model Developmentmentioning
confidence: 99%
“…For the assumed earthquake events, the BSSA14 model with the median value shows the PGA in the range of 0.1-0.4 g considering the site amplification effects with average shear wave velocity from surface to 30-m depth (V s30 ) of 330 m/s. If the larger area than Chiang Mai Municipality is a case study, the variation of the site amplification effects should be considered (Bonilla et al, 1997;De Risi et al, 2019).…”
Section: Seismic Building Damage Calculation Using Capacity Spectrum mentioning
confidence: 99%